2018
DOI: 10.1101/373365
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The soil microbial food web revisited with metatranscriptomics - predatory Myxobacteria as keystone taxon?

Abstract: 1 1 2 3 4 6 7 8 9 10 Abstract Trophic interactions in the microbial food web of soils are crucial for nutrient and carbon cycling. Traditionally, protozoa are considered the major micropredators of bacteria in soil. However, some prokaryotes, such as Myxobacteria and Bdellovibrio are also famous for bacterivorous life style. Until recently, it was impossible to assess the abundance of pro-and eukaryotic micropredators in soils simultaneously. Using a metatranscriptomic three-domain profiling of small subunit r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…Most of the myxobacterial sequences from subtropical and tropical forest soil in this study were uncultured. Our results showed that the abundance of Sorangiineae and Nannocystineae were much higher than that of Cystobacterineae, which is consistent with the results indicated by prokaryotic 16S rRNA transcripts [ 48 ]. The low abundance of Cystobacterineae illustrated by culture-independent methods indicates the biases of the culture-dependent method, because species from Cystobacterineae are frequently isolated [ 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…Most of the myxobacterial sequences from subtropical and tropical forest soil in this study were uncultured. Our results showed that the abundance of Sorangiineae and Nannocystineae were much higher than that of Cystobacterineae, which is consistent with the results indicated by prokaryotic 16S rRNA transcripts [ 48 ]. The low abundance of Cystobacterineae illustrated by culture-independent methods indicates the biases of the culture-dependent method, because species from Cystobacterineae are frequently isolated [ 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…Both groups likely respond to similar changes in their surrounding habitat as shown before (Yao et al, 2011;Wang et al, 2019b). Predatory bacteria prey on a diverse range of bacteria (Morgan et al, 2010;Petters et al, 2018) and therefore reduce Significance levels are denoted with *P < 0.05, **P < 0.01, ***P < 0.001. Standardized total effects (direct plus indirect effects) calculated by the SEM are displayed below the SEM.…”
Section: Discussionmentioning
confidence: 96%
“…These predatory bacteria are also selective in their prey choice (Morgan et al, 2010), and might therefore promote AOB through preying on their bacterial competitors. A strong positive link between predatory/exoparasitic bacteria with phagotrophic protists might be explained by the fact that both predator groups follow abundances of their main prey: bacteria (Geisen et al, 2018;Petters et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Despite being considered keystone taxa within microbial communities (Petters et al, 2021), the extent of myxobacterial bacterivory and its contribution to nutrient cycling within microbial food webs remains unknown. These results further demonstrate myxobacterial eavesdropping on prey signaling molecules and provide insight into how responses to exogenous signals might correlate with prey range of myxobacteria.…”
Section: Discussionmentioning
confidence: 99%